Static analysis of a balanced armature receiver - Ziolkowski, Marcin; Kwiatkowski, Wojciech; Gratkowski, Stanislaw; Ziolkowski, Marek (Compel, 2018)
Purpose A balanced armature receiver (BAR) as a special type of electromagnetic acoustic transducers plays a significant role in reproduction of music and speech, active noise control in modern hearing aid and in contemporary in-ear monitors. This paper aims to present a static analysis of the balanced armature receiver based on the lumped network approach (LNA) and the finite element method (FEM). Design/methodology/approach In this paper, the LNA and two-dimensional FEM are applied to model deflections of the BAR’s armature from the equilibrium position. Results of calculations are compared with measurements. Findings The derived analytical formulas and developed procedure allow for calculation of the armature deflection. Originality/value Comparing to the previous papers, the reluctance’s nonlinearity of the armature has been considered.